Comparing texture and digestion properties between white and brown rice of indica cultivars preferred by Chinese consumers - Min Huang (Nature Portfolio, 2021)
Abstract The consumption of good tasting rice, mainly soft-textured white rice with low amylose content, has substantially increased in China as living standards improve. However, this diet change may increase the risk of developing type II diabetes because the soft-textured white rice is generally less resistant to digestion and has a higher glycemic index. In contrast, intake of brown rice is inversely associated with type II diabetes risk. This study was conducted to test the possibility that brown rice processed from soft-textured cultivars has both acceptable texture and improved health benefits. Texture and digestion properties were compared between white and brown rice of five indica cultivars preferred by Chinese consumers. Mean hardness was 33% higher while mean springiness was 5% lower for cooked brown rice than for cooked white rice. As compared to cooked white rice, cooked brown rice had a 41% longer mean active digestion duration but 31% lower mean glucose production rate and 11% lower mean total glucose production from starch digestion. However, the differences in texture and starch digestion properties between cooked brown and white rice were affected by cultivar identity. Brown rice processed from suitable cultivars with both a relatively thinner bran layer and relatively higher grain amylose content met consumer requirements in terms of acceptable texture and improved health benefits.